Development of Android Multimedia “TRIGO-MEDIA” Using AIR Learning Model to Improve Mathematical Problem-Solving Ability - Gunawan Gunawan; Aprilia Nurul Chasanah; Syita Fatih 'Adna (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to determine the validity, practicality, and effectiveness of the development of the android multimedia "TRIGO-MEDIA" using the Auditory, Intellectually, Repetition (AIR) learning model to improve the mathematical problem-solving ability. This research is a development research using the ADDIE development model. The subjects of this study were students of classes X MIPA 1 and X MIPA 2 in SMA Negeri 2 Magelang. The results showed that the multimedia developed was in a very valid category with a percentage of 91.03% of the material validity and 90.41% of the media validity, multimedia was in a very practical category with a percentage of 82.54%. Then, multimedia meets the effective aspect with a significant difference between the control and experimental class (the average TKPMM value in the control class is 51.71 and the experimental class is 80.23). This can be concluded that the development of the Android multimedia "TRIGO-MEDIA" uses the learning model of the Auditory, Intellectually, Repetition (AIR) that is valid, practical, and effective to improve the mathematical problem-solving ability of students.